A comparative analysis of location and non-location-bounded strategic asset seeking in emerging and developed market MNEs: An application of new internalization theory. Issue 2 (April 2020) - Sutherland, Dylan; Anderson, John; Hu, Zheyuan
Highlights: Do EMNEs have a stronger strategic asset seeking FDI orientation than DMNEs? What are the properties of the strategic assets they actually seek? Are they similar or dissimilar to those of DMNEs? EMNE theory conceals important predictions regarding differences in the location-boundedness properties of strategic assets sought by EMNEs. Analysis of international M&A deals shows how strategic asset location-boundedness properties in target firms influences deal-making choices. Abstract: Do emerging market (E)MNEs have a stronger strategic asset seeking FDI orientation than developed market (D)MNEs? If so, what are the properties of the strategic assets they actually seek and are they similar or dissimilar to those of DMNEs? Drawing from new internalization theory, we show that lying concealed within some mainstream EMNE models are important predictions regarding differences in the location-boundedness properties of the strategic assets sought by EMNEs compared with DMNEs. Using multinomial logit modelling on 2414 international M&A deals, we explore how acquirer characteristics shape location-bounded (trademark) and non-location bounded (patent) strategic asset seeking choices. In general, we find evidence that EMNEs have a comparatively stronger patent but weaker trademark seeking orientation than DMNEs. We discuss implications for EMNE related theory, focusing on the qualitative differences in asset seeking orientation between EMNEs and DMNEs.